O-092 Sperm phenotype, ICSI outcome and genetic diagnosis in case of severe asthenozoospermia with multiple morphological abnormalities of the flagellum. (6th August 2021) - Ferreux, L; Bourdon, M; Chargui, A; Schmitt, A; Stouvenel, L; Lorès, P; Ray, P; Lousqui, J; Pocate, K; Santulli, P; Dulioust, E; Toure, A; et al.
Abstract: Study question: What are the feasibility and outcome of ICSI in case of presumably genetic severe asthenozoospermia with Multiple Morphological Abnormalities of the Flagellum (MMAF phenotype)? Summary answer: ICSI outcome for couples with MMAF phenotype does not differ from that of other couples requiring ICSI, regardless to the genetic etiology What is known already: Severe asthenozoospermia, especially when associated with multiple morphological abnormalities of the sperm flagellum (MMAF phenotype), results in male infertility. Recent findings confirm that a genetic etiology is frequently responsible for this phenotype. In such situations, pregnancies can be obtained using ICSI. However, few studies have provided detailed analyses of the flagellar ultrastructural defects underlying this phenotype, of its genetic etiologies and of the results of ICSI in such cases of male infertility. Study design, size, duration: We performed a retrospective study including 25 infertile men showing severe asthenozoospermia associated with a MMAF phenotype identified through standard semen analysis. These men were recruited from an academic center for Assisted Reproduction in Paris between 2009 and 2017. Transmission electron microscopy (TEM) and Whole Exome Sequencing (WES) were performed in order to precise the sperm ultra-structural phenotype and identify causal mutations, respectively. Twenty of the 25 patients benefited from assisted reproductive therapy by ICSI. Participants/materials, setting, methods: MMAF patients were recruited based on reduced sperm progressive motility and increased frequencies of absent, short, coiled or irregular flagella, in comparison with fertile control men. A quantified analysis of the ultrastructural defects was performed for the MMAF patients and for fertile control men. ICSI results for the MMAF patients were compared to those of 528 ICSI attempts performed for non-MMAF individuals considering the sperm parameters and the distribution of ultrastructural axonemal anomalies. Main results and the role of chance: Thorough categorization by TEM analysis of the flagellar anomalies found in these patients brought important precisions about the structural defects underlying asthenozoospermia and sperm tail abnormalities detectable through standard microscopy. In particular, absence of the central pair of axonemal microtubules was the predominant anomaly, observed significantly more frequently than in control men (p < 0.01). Exome sequencing performed for 24 of the 25 patients (96%), identified in ten of them homozygous or compound heterozygous mutations that were described to be pathogenic (CFAP43, CFAP44, CFAP69, DNAH1, DNAH8, AK7, TTC29, MAATS1). A majority of those patients (55.5%, 5/9) displayed the most severe ultra-structural defects of the axoneme. Forty ICSI attempts were performed for 20 MMAF patients. A hypo-osmotic swelling (HOS) test was required in 13 cycles (5 couples). Fertilization rate in MMAF group (65.7%) was not statistically different from the rate obtained for non-MMAF patients (66.0%) and did not differ according to the flagellar phenotype, nor to the use of HOS test, nor to the genotype. Clinical pregnancy rate per embryo transfer did not significantly differ between the MMAF group (23.3%) and the ICSI control group (37.1%). To date, 11 healthy babies were born among 20 MMAF patients. Limitations, reasons for caution: The outcome of ICSI procedure was retrospectively assessed on a small sample and may be susceptible to recall bias. Moreover, TEM analysis was not available for some of the patients due to too low sperm concentration, and WES results are not yet available for all men included. Wider implications of the findings: Couples requiring ICSI for presumably genetic severe asthenozoospermia should benefit precociously from appropriate phenotypic and genetic investigations. So far ICSI results appear similar to those observed in other ICSI indications. Identifying a genetic etiology and its mode of inheritance allows providing to these couples a most often reassuring genetic counseling. Trial registration number: Not applicable